2011
DOI: 10.1007/s10096-011-1414-8
|View full text |Cite
|
Sign up to set email alerts
|

The first detection of Toxoplasma gondii DNA in environmental fruits and vegetables samples

Abstract: Toxoplasma gondii infections are prevalent in humans and animals all over the world. The aim of the study was to estimate the occurrence of T. gondii oocysts in fruits and vegetables and determine the genotype of the parasites. A total number of 216 fruits and vegetables samples were taken from shops and home gardens located in the area of northern Poland. Oocysts were recovered with the flocculation method. Then, real-time polymerase chain reaction (PCR) targeting the B1 gene was used for specific T. gondii d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 40 publications
1
75
2
4
Order By: Relevance
“…vaccination) it is important to collect and analyse information obtained from epidemiological investigations and surveys that standardise the sample matrix (brain, heart, lungs), the analytical method (direct methods preferentially) and the target population (species and risk categories). In addition, there is a lack of information on the contamination of vegetables and fruit and drinking water by Toxoplasma oocysts shed by cats (Dumetre and Darde, 2003;Lass et al, 2012). There is the need to investigate these transmission routes.…”
Section: Discussionmentioning
confidence: 99%
“…vaccination) it is important to collect and analyse information obtained from epidemiological investigations and surveys that standardise the sample matrix (brain, heart, lungs), the analytical method (direct methods preferentially) and the target population (species and risk categories). In addition, there is a lack of information on the contamination of vegetables and fruit and drinking water by Toxoplasma oocysts shed by cats (Dumetre and Darde, 2003;Lass et al, 2012). There is the need to investigate these transmission routes.…”
Section: Discussionmentioning
confidence: 99%
“…Nesses, a toxoplasmose é adquirida principalmente pela via oral, por meio da ingestão de cistos presentes em carnes consumidas cruas ou mal cozidas, ou de oocistos excretados nas fezes de felídeos infectados e que podem contaminar frutas e verduras, água e solo 2, 3,4 .…”
Section: Introductionunclassified
“…Another study reported the detection of Toxoplasma DNA by real-time PCR in 9.7% of fruit and vegetable samples collected in Poland (Lass et al, 2012). Al-Megrin (2010) reported a 1.1% prevalence of T. gondii oocysts on leafy vegetables in Saudi Arabia.…”
Section: Surveillance Studies and Outbreaks Associated With Fresh Promentioning
confidence: 99%